Assistance in Increasing Community Livelihoods through Optimizing the Business Role of Village Owned Enterprises - Mubarokah, Laily; Ningrum, Ifa Khoiria; Hidayah, Siti Nur (IDFoS Indonesia, 2021)
Abstract The purpose of empowerment program through Village Owned Enterprises in Bandungrejo Village, Ngasem Sub-District, Bojonegoro Regency were 1) Contributing to improve community welfare through replicating the successful implementation of previous programs in improving the livelihoods of rural communities around the JTB Project to other villages; 2) Realizing the principle of equity and justice in the implementation of community development programs that were not limited to the project area but also to communities outside the project area in accordance with regional policy priorities; and 3) Maintaining good relations with the surrounding community and local government so that the business is able to run well. The method used was Participatory Action Research (PAR). The results of the assistance program were the existence of a joint commitment and support from various parties, including the Village Government, BPD, Village Owned Enterprises managers, Bandungrejo Village Government had planned for BUMDes which would only be budgeted in 2021 for 300 million. Managers needed to have capacity building regarding roles, duties, principals and functions, also had organizational governance. From the above activities, research on book preparation, as well as two book review experts who are competent in their fields strongly support book review activities Keywords: Community Assistance, Business, Village Owned Enterprises